Perilous policing: an analysis of the Resident Evil Series - Steinmetz, Kevin F. (Critical criminology, 2023)
The current analysis takes seriously representations of the police throughout the Resident Evil series, a hallmark horror game franchise. Drawing from both cultural criminology and gothic criminology, this study involves a grounded theory-based analysis of representations of the police throughout the series, considering them to be culturally salient indicators of attitudes, beliefs, and anxieties concerning police and related institutions of social control in both the USA and Japan. Results of this analysis indicate that the series portrays the police in two ways: (1) stalwart or professional and capable protectors championing good and (2) fallible or corruptible and inadequate. The study interprets these themes through prior research on police occupational culture and identity as well as the American and Japanese historical contexts in which the series emerged, developed, and gained popularity. The analysis also considers how the subversion of the police as protectors in Resident Evil reflects deep seated anxieties about modern policing while also celebrating police violence.